Sinkronisasi Regulasi Green Bond Sebagai Pembiayaan untuk Konversi Baterai Kendaraan Listrik di Indonesia - Budi Endarto (Jurnal Penelitian Hukum De Jure, 2024)
Transportation is still the largest emission-contributing sector in Indonesia. However, the Government has set an aggressive electrification target in the transportation sector if it needs to be balanced with a financing scheme for energy conversion towards battery electric vehicles (BEV). For this reason, BEV conversion industry players should utilize green bond financing schemes. The main issue lies in the need for more alignment between EV conversion industry regulations and financing models for the sector. However, the Government needs to harmonize rules and coordination among sectoral institutions such as the OJK, Ministry of Finance, Ministry of Industry, and Ministry of Transportation. Especially concerning Regulation Number 39 of 2023 regarding the Conversion of Fuel-Powered Motorcycles into Battery-Based Electric Motorcycles, and Minister of Transportation Regulation Number 15 of 2022 regarding Motor Vehicle Conversion to formulate green bonds as an alternative financing option for BEV programs. The method used in this writing is normative legal research of the exploratory type with a statutory and conceptual approach. The result shows that through the synchronization model of green bond financing regulations with the battery electric vehicle conversion regulation and coordination between sectoral institutions, it is expected to accelerate the commitment to realize net zero emission and as an effort to mitigate the energy crisis and reduce fuel energy subsidies in Indonesia.